The Effectiveness of China’s Anti-Food Waste Campaign on University Canteens - Weihao Chen (Studies in Social Science & Humanities, 2024)
Food waste in university canteens is a significant issue in China, contributing to environmental degradation and financial inefficiencies. In response, the Chinese government and universities have implemented comprehensive anti-food waste campaigns aimed at reducing waste volumes and promoting sustainable consumption practices. This paper examines the effectiveness of these measures, focusing on their impact on student behavior, operational efficiencies, and broader environmental benefits. Key initiatives include the introduction of portion control options, educational programs, and advanced waste monitoring technologies. Through case studies and comparative data analysis, the study highlights significant reductions in food waste, cost savings, and improved environmental outcomes. The findings underscore the importance of combining technological innovation with behavioral change to achieve long-term sustainability in campus dining.